Die Agrarstruktur der Bundesrepublik Deutschland - Ansätze zu einer regionalen Typologie - Laux, Hans-Dieter; Thieme, Günter (ERDKUNDE, 1978)
The agrarian structure of the Federal Republic of Germany is characterized by considerable regional disparities. It is the aim of this contribution to describe and analyse these regional differences through a typology on the basis of a sample of 612 communities. Proceeding from the hypothesis that the agrarian structure of any region is determined not only by its agricultural situation but also by its socio economic situation in general, in the first step of the investigation 46 variables were subjected to factor analysis. These variables are associated with the following topics. Agriculture: farm size, labour supply, socio-economic structure of holdings, extent of mechanization, land use and livestock orientation;non-agricultural sector: degree of urbanization, non-agricultural labour supply, and distance to urban centres. Eight factors were extracted altogether, explaining 83.69% of the total variance. Factor 1 is to be interpreted as the factor of the socio-economic structure of the communities, factors 2 and 3 each represent different aspects of the structure of agricultural holdings, factor 2 stressing the contrast between small and large property, factor 3 describing the proportion of medium-sized holdings. The intensity of labour input in agriculture is characterized by factor 6, whereas land use orientation, non-agricultural labour supply, and the distance to urban centres are successively represented by factors 4, 5, and 7. In a second step the typology of the agrarian structure was carried out by means of distance grouping. Being the most important dimensions, factors 1, 2, 3, and 6 were selected for the grouping process. The results of this multi dimensional classification are shown in table 4. The spatial distribution of the structural types (cf. fig. 6, Suppl. VI) shows clear regional differences between Northern Germany (Schleswig-Holstein, Lower Saxony, North Rhine-Westphalia), South West Germany (Hesse, Rhineland-Palatinate, Saar, Baden-Wiirttemberg), and Bavaria. In particular the following types show a striking regional concentration: groups 1 and 2 with an overall favourable agrarian structure are almost exclusively to be found in Northern Germany, whereas group 6, which faces grave agricultural and socio-economic problems, is a typically Bavarian phenomenon. On the other hand, groups 7 and 8, characterized by small holdings and a high proportion of part-time farming are mostly concentrated in the gavelkind areas of South West Germany.